EFFORTS TO IMPROVE TEACHERS' ABILITIES IN APPLYING CONTEXTUAL LEARNING THROUGH FOCUS GROUP DISCUSSION - Bakri Melpi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the learning process which was still dominated by the teacher as a source of knowledge through conventional methods in the form of lecturing; as a result, students became passive during the learning process. Ideally, learning should be able to increase students' understanding about the material and their understanding about the relationship between the material and the student's environment. Referring to these problems, it was necessary to apply a method that helped teachers to improve the learning quality. It was hoped that focus group discussions improved the teachers’ ability to apply contextual learning. This research was a classroom action research. The research was carried out on teachers at SDN 019 Sungai Gantang from February to March 2020. The research subjects were 17 teachers and the instrument was an observation sheet. The results showed that the teachers’ ability to implement contextual learning through focus group discussions increased from 80.25% (with Good category) in cycle I to 84.45% (with Very Good category) in cycle increased II. Based on the results of this research, it was concluded that focus group discussions improved teachers’ ability in implementing contextual learning.